Strategi Pemasaran Pendidikan dalam Meningkatan Mutu Sekolah di SMP Negeri 9 Ambon - Mesak Hattu; Anna Maria Ngabalin (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Marketing strategy is one way to win competitive advantage on an ongoing basis both for a company that produces goods and services as well as for an educational institution. The education marketing strategy can be seen as one of the bases used in compiling overall program planning in providing satisfaction to stakeholders and the community as users of educational services. The purpose of this research is to describe the strategy and implementation of educational marketing in improving the quality of schools in SMP Negeri 9 Ambon. The approach used in this research is a qualitative approach with a descriptive research type. Collecting research data through interviews, observation, documentation and triangulation techniques. Data analysis uses reduction techniques, presentation and data verification. The results of this study indicate that; (1) the form of an educational marketing strategy, marketing promotion has been well implemented, namely by understanding the needs of consumers who use educational services, (2) the implementation of the educational marketing strategy at SMP Negeri 9 Ambon on each indicator of the marketing mix strategy has been running well although there are some weaknesses that are still found.